Alternative clinical specimens for the detection of SARS‐CoV‐2: A rapid review. (22nd October 2020) - Comber, Laura; Walsh, Kieran A.; Jordan, Karen; O'Brien, Kirsty K.; Clyne, Barbara; Teljeur, Conor; Drummond, Linda; Carty, Paul G.; De Gascun, Cillian F.; Smith, Susan M.; Harrington, Patricia; Ryan, Máirín; et al.
Summary: The collection of nasopharyngeal swabs to test for the presence of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is an invasive technique with implications for patients and clinicians. Alternative clinical specimens from the upper respiratory tract may offer benefits in terms of collection, comfort and infection risk. The objective of this review was to synthesise the evidence for detection of SARS‐CoV‐2 ribonucleic acid (RNA) using reverse transcription polymerase chain reaction (RT‐PCR) tested saliva or nasal specimens compared with RT‐PCR tested nasopharyngeal specimens. Searches were conducted in PubMed, Embase, Europe PMC and NHS evidence from December 2019 to 20 July 2020. Eighteen studies were identified; 12 for saliva, four for nasal and two included both specimen types. For saliva‐based studies, the proportion of saliva samples testing positive relative to all positive samples in each study ranged from 82.9% to 100%; detection in nasopharyngeal specimens ranged from 76.7% to 100%; positive agreement between specimens for overall detection ranged from 65.4% to 100%. For nasal‐based studies, the proportion of nasal swabs testing positive relative to all positive samples in each study ranged from 81.9% to 100%; detection in nasopharyngeal specimens ranged from 70% to 100%; positive agreement between specimens for overall detection ranged from 62.3% to 100%. The results indicate an inconsistency in the detection of SARS‐CoV‐2 RNA in the specimen types included, often with neither the index nor the reference of interest detecting all known cases. Depending on the test environment, these clinical specimens may offer a viable alternative to standard. However, at present the evidence is limited, of variable quality, and relatively inconsistent.